Analýza klíčových faktorů soudobé „finanční krize“ a jejich vlivu na vývoj světové ekonomiky - Rejnuš, Oldřich (Univerzita Pardubice, 2012)
The paper deals with key factors of contemporary „financial crisis“ and their impacts on the development of world economy. First of all, the most important factors that caused the crisis are identified and their share on formation of contemporary negative development trends of financial system is analyzed. Afterwards, their consequences on the development of world economy are assessed both from practical and theoretical points of view. Pursued analysis is focused on two basic spheres. First of all, it deals with negative economic factors that are explored from the point of view of all sorts of economic subjects – it means households, companies and states. And what is especially important, it is focused on man himself (or herself) as he or she has “primary” influence on the development of world economy and thus the whole human society. Finally, the matter of effectiveness of up-to now used anti-crisis measures are discussed, where possible negative impacts that can be caused by their long-term use are assessed. Last of all, possibility of global financial crisis that might cause collapse of world economy is outlined.
Analysis of key factors of contemporary „financial crisis" and its impacts on development of world economy
Keywords: financial crises; risk factors; economic crisis; financial markets; global economy; market economy; state regulation; quantitative easing; structure products; inflation